HUBUNGAN KEBIASAAN MEROKOK TERHADAP DAYA TAHAN PADA CLUB BOLA VOLI MITRA JUNIOR KEC BALAI JAYA KABUPATEN ROKAN HILIR - Riko Wibisono; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that the smoking habit of volleyball athletes has a major impact on the stamina while playing, the habit after smoking immediately without resting first. The purpose of this research was to determine the relationship between smoking habits and stamina in junior partner volleyball clubs, Balai Jaya sub-district, Rokan Hilir regency. The population in this research consisted of 12 junior partner volleyball athletes using the total sampling technique. The instrument in this research was a closed questionnaire and a beep test. Based on the analysis of the normality test, the X data produces LoMax of 0.241 and Ltable of 0.242. while variable Y produces LoMax of 0.113 and Ltable of 0.242. This means LoMax < Ltable. Based on statistical data analysis, the data is normally distributed. Based on the above analysis requirements test, the hypothesis test on variable X against variable Y data is 0.343 < 0.735 Rhitung < R table data. Thus, there is no relationship between smoking habits and stamina in junior partner volleyball clubs, balai jaya sub-district, rokan downstream district.Key Words: Smoking Habits, Stamina, Volleyball